Efficacy of misoprostol in relation to uterine position in the treatment of early pregnancy failure. Issue 2 (15th February 2013) - Reif, Philipp; Tappauf, Carmen; Panzitt, Thomas; Haas, Josef; Lang, Uwe; Klaritsch, Philipp
Abstract: Objective: To evaluate the efficacy of misoprostol in the treatment of missed or incomplete abortion in relation to uterine position. Methods: In a retrospective cohort study, misoprostol was evaluated as first‐line treatment for missed and incomplete abortion before 13 gestational weeks. Between 2009 and 2011, women received 600 μg of sublingual misoprostol for missed abortion or 400 μg for incomplete abortion. Follow‐up examinations were performed 7–10 days later, with the option of a second administration of misoprostol. Success was defined by the absence of vaginal bleeding or sonographic signs of incomplete abortion, and falling levels of β‐human chorionic gonadotropin. Results: In total, 111 women were included in the study. A single‐dose regimen was effective for 73 (65.8%) women. The overall success rate, including repeat doses, was 73.0% (81/111). There were no significant differences in treatment success between women with missed abortion and those with incomplete abortion (56/89 [62.9%] vs 18/22 [81.8%]; P = 0.152). Anteverted uterine position was associated with significantly higher success rates compared with diverging position (62/86 [72.1%] vs 4/18 [22.2%]; P = 0.001). Conclusion: Misoprostol is an effective treatment for early pregnancy failure. Uterine position might impact the success of medical treatment for missed abortion.